The subtle co-catalytic intervention of benzophenone in radical cation mediated cyclization - an improved synthesis of 2-(3 ',4 '-Dimethoxyphenyl) indoline - Ariffin, Azhar; Hadi, A.H.A.; Thomas, N.F.; Kee, C.H.; Awang, Khalijah; Weber, J.F.F.; Lim, C.G.; Mukhtar, M.R. (2008)
The addition of benzophenone to a FeCl(3)/CH(2)Cl(2) mixture in the presence of 3',4'-dimethoxy-2-acetamidostilbene 17 unexpectedly leads to a dramatic improvement in yield of the indoline 20 from 38% (previously reported by us) to 75.4%, after careful examination of a variety of reaction conditions. A catalytic cycle has been proposed that involves not only stilbene radical cations but also Fe(2+) promoted benzophenone ketyl radical formation which enhances cyclisation, suppresses dimerization and accounts for the virtually quantitative recovery of the benzophenone.